Notified occupational mental disorders: associations with health and income. (4th February 2023) - Ladegaard, Y; Dalgaard, V L; Conway, P M; Eller, N H; Skakon, J; Maltesen, T; Scheike, T; Netterstrøm, B
Abstract: Background: Studies indicate that workers' compensation claim processes may affect patients' health negatively. However, few studies focus on patients with mental health claims, and the claim process varies between countries. Aims: The aims of this study were to examine whether being notified to the Danish Labour Market Insurance with an occupational mental health condition was associated with changes in visits to the general practitioner (GP), use of medicine and annual income. Methods: Study participants were 965 patients with a mental disorder examined at a department of occupational medicine. Of these, 669 patients were notified with an occupational mental disorder, 296 were not. Health-related outcomes, including GP visits and prescriptions of psychotropic drugs, were estimated at baseline during the year of medical examination, while annual income was estimated a year before the examination. The follow-up was the year after the year of examination for all outcomes. Outcomes were collected from the Danish National Bureau of Statistics. Analyses were conducted using Poisson regression and conditional logistic regression. Results: All measured outcomes decreased from baseline to follow-up in both groups. These changes were not significantly different depending on notification status at baseline. Conclusions: This study suggests that being notified with an occupational mental disorder does not significantly affect health-related outcomes. A significant decrease in annual income over time was seen in both groups, the notified and the unnotified group, highlighting the importance of providing support to all employees with a mental disorder. Abstract : Work-related mental disorders are a leading cause of workers' compensation claims in Western countries. This study examines if the process of being notified has negative consequences for the worker in terms of changes in health status and annual income. We did not find that the notification process had significant negative effects on either workers' health or annual income. Among workers with a mental disorder, annual income decreased in both the notified and the unnotified group.